Pengaruh Manajemen Modal Kerja Terhadap Profitabilitas (Studi pada Perusahaan Food and Beverages yang Listing di BEI periode 2007-2011) - Nurul Aini (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The study aims at examining the effect on working capital management as well on profitability of the Food and Beverages companies listed in Indonesia Stock Exchange. This research described the influence of four independent variables namely Inventory turnover period, Receivables Conversion Period, Payables Defferal Period, and Cash conversion cycle on the return on asset of firms. This research was explanotory reasearch. It was included in the type of quantitave population research. This research used 13 firms period of 5 years from 2007- 2011. Multiple linear regression was used to analyze the data. The result showed that there was a strong negative relationship between Inventory turnover period, Payables Defferal Period, and Cash conversion cycle and return on asset of the firms. Receivables Conversion Period did not affect on the return on asset of the firms. It meant that as the cash conversion cycle increases it will lead to decrease return on asset of the firm. Therefore, managers can create positive value for the shareholders by reducing the cash conversion cycle to a possible minimum level. Keywords : Working Capital, Profitability, Cash Conversion Cycle